The Relationship Between The Quality of Physiotherapy Services To The Level of Satisfaction of Patients With Neuromuscular Case Practice Self Physiotherapy In Malang Raya - Azzahra Anindya AisyaPutri; Safun Rahmanto; Kurnia Putri Utami (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
The purpose of this study was to determine the relationship between service quality and patient satisfaction levels. The sample is 30 respondents obtained by using convenience sampling. The research design is analytic observation with a cross-sectional approach. The results of the Spearman test obtained a p value of 0.000 <0.05. This shows that there is a relationship between the quality of service and the level of patient satisfaction. In conclusion, a relationship was found between the quality of service and the level of patient satisfaction with neuromuscular cases at the Mandiri Physiotherapy Clinic in Malang Raya